Elevated ATP via enhanced miRNA-30b, 30c, and 30e downregulates the expression of CD73 in CD8+ T cells of HIV-infected individuals - Shahbaz, Shima; Okoye, Isobel; Blevins, Gregg; Elahi, Shokrollah (PLoS pathogens, 2022)
CD8 + T cells play a crucial role against chronic viral infections, however, their effector functions are influenced by the expression of co-stimulatory/inhibitory receptors. For example, CD73 works with CD39 to convert highly inflammatory ATP to adenosine. However, its expression on T cells in the context of viral infections has not been well defined. Here, we analyzed the expression of CD73 on human T cells in a cohort of 102 HIV-infected individuals including those on antiretroviral therapy (ART), ART-naïve, and long-term non-progressors who were not on ART. We found that the frequency of CD73 + T cells was markedly lower among T cell subsets (e.g. naïve, effector or memory) in the peripheral blood of all HIV-infected individuals. Notably, CD73 was decreased at the cell surface, intracellular and gene levels. Functionally, CD8 + CD73 + T cells exhibited decreased cytokine expression (TNF-α, IFN-γ and IL-2) upon global or antigen-specific stimulation and impaired expression of cytolytic molecules at the gene and protein levels. In contrast, CD8 + CD73 + T cells expressed elevated levels of homing receptors such as CCR7, α4β7 integrin, which suggests a migratory advantage for these cells as observed in vitro . We also observed significant migration of CD73 + CD8 + T cells into the cerebrospinal fluids of multiple sclerosis (MS) patients at the time of disease relapse. Moreover, we found that elevated levels of ATP in the plasma of HIV-infected individuals upregulates the expression of miRNA30b-e in T cells in vitro . In turn, inhibition of miRNAs (30b, 30c and 30e) resulted in significant upregulation of CD73 mRNA in CD8 + T cells. Therefore, we provide a novel mechanism for the downregulation of CD73 via ATP-induced upregulation of miRNA30b, 30c and 30e in HIV infection. Finally, these observations imply that ATP-mediated downregulation of CD73 mainly occurs via its receptor, P2X1/P2RX1. Our results may in part explain why HIV-infected individuals have reduced risk of developing MS considering the role of CD73 for efficient T cell entry into the central nervous system.